1998
DOI: 10.1144/gsl.sp.1998.133.01.04
|View full text |Cite
|
Sign up to set email alerts
|

The geological history of the southern Wessex Basin — a review of new information from oil exploration

Abstract: Mapping of intervals between the base of the Aylesbeare Mudstone (Permian or BUTLER, M. 1998. The geological history of the southern Wessex Basin -a review of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 21 publications
1
28
0
Order By: Relevance
“…2). The boundary between the BSPBF and the underlying Aylesbeare Mudstone Group (Early Triassic) is an unconformity (Holloway et al, 1989), which is most clearly apparent from seismic surveys and well data farther east in the Wessex Basin (Butler, 1998). The unconformity between the BSPBF and the OSF is considered to be equivalent to the Hardegsen Unconformity in the Germanic Basin (Holloway et al, 1989;Butler, 1998).…”
Section: The Sherwood Sandstone Group Of Devonmentioning
confidence: 99%
See 2 more Smart Citations
“…2). The boundary between the BSPBF and the underlying Aylesbeare Mudstone Group (Early Triassic) is an unconformity (Holloway et al, 1989), which is most clearly apparent from seismic surveys and well data farther east in the Wessex Basin (Butler, 1998). The unconformity between the BSPBF and the OSF is considered to be equivalent to the Hardegsen Unconformity in the Germanic Basin (Holloway et al, 1989;Butler, 1998).…”
Section: The Sherwood Sandstone Group Of Devonmentioning
confidence: 99%
“…This major hiatus represents the unconformity surface beneath the OSF. In the central and eastern parts of the Wessex Basin, the unconformity surface locally truncates faults in the underlying succession (Butler, 1998). Holloway et al (1989) suggested that there was erosion at this time, in order to explain the absence of conglomerates below the OSF in the central parts of the Wessex Basin, although Smith & Edwards (1991) argued that this could equally well be due to non-deposition or to lateral facies changes.…”
Section: The Sherwood Sandstone Group Of Devonmentioning
confidence: 99%
See 1 more Smart Citation
“…There are two alternative lines along which to take the southern boundary of the MMC: the first is the line south of which the Old Red Sandstone facies seen in core and cuttings samples from released wells appears to be more indurated and is possibly equivalent to the Devonian sandstones of north Devon; and the second is the better-defined northern boundary of the subcrop of highly deformed Devonian and Carboniferous shales identified by well and borehole information beneath the Permo-Trias. In Dorset, this boundary also marks the northern extent of the thick Permian Aylesbeare Mudstone sequence (Butler 1998). This second alternative is taken as the boundary of the Variscide Rhenohercynian Terrane and the southern margin of the MMC.…”
Section: Definition Of the Midlands Microcratonmentioning
confidence: 99%
“…Similar to other Mesozoic depocentres within the UK, the Wessex Basin has been subjected to marked Alpine deformation and inversion, but it is not the purpose of this paper to discuss the tectonism in any detail. For more detailed descriptions of the tectonic history of this area, see Beeley and Norton (1998), Butler (1998), Chadwick (1986), Chadwick et al (1983), Hamblin et al (1992), Harvey and Stewart (1998), Hawkes et al (1998), Karner et al (1987), Lake and Karner (1987), Law (1998), Smith and Hatton (1998), Underhill and Stonely (1998), Whittaker et al (1985) and Zeigler (1990).…”
Section: Geographical and Structural Settingmentioning
confidence: 99%